Evidence of The Successful Conservation of Enhalus Acoroides in Terms of The Diversity of Bivalves on The Coast of East Lombok - Rizal Umami; Agil Al Idrus (Jurnal Biologi Tropis, 2023)
The existence of seagrass in coastal areas can affect marine biota that live around it. Seagrass has an important role as an area of ​​care, spawning, and protection. This study aims to determine the success of conserving seagrass beds of the Enhalus acorodies species in terms of bivalve diversity on the south coast of East Lombok. The research was conducted using transect and observation methods. The data obtained were analyzed using evenness index, diversity index, and species richness. The results of the study found 10 types of Bivalves in Poton Bako. Bivalves diversity index is included in the medium category of 2,228. The evenness index of bivalves was 0.409 in the low category. Then, the species richness index is 1.653 in the low category. The species diversity of Bivalvia in seagrass beds in Poton Bako is still relatively moderate so that the sustainability of the seagrass species Enhalus acoroides can be said to be maintained. The existence of a feed source or substrate derived from the remains of seagrass is used as a source of feed. The conservation of Enhalus acoroides seagrass needs to be maintained so that it has an impact on the survival and diversity of Bivalves in the area.